Ethnobotany, Propagation and Conservation of Medicinal Plants in Ghana (2012)
Medicinal plants and plant-based medicines are widely used in traditional cultures all over Ghana and they are becoming increasingly popular in modern society as natural alternatives to synthetic chemicals. This paper studied the ethnobotany of medicinal plants through a socio-economic survey. Seed germination experiments were also carried out on selected medicinal plant species. It was found that the herbal medicine industry was a major source of income for 82% of the respondents. Almost 50% of the respondents were women with majority of them involved in marketing of the medicinal plant products. Out of 160 plant species marketed, 129 were collected in Ghana with Kumasi and Accra being the major marketing centres. Most of the species have multiple curative properties with over 46 diseases purported to be cured by herbal medicine. Over 100 species were reported to be in high demand, scarce or unavailable. Among the reported constraints to availability of medicinal plants were lack of cultivation, unsustainable harvesting, deforestation, wildfire and urbanization. Studies on seed germination showed that seven species out of the ten selected for conservation had good germination, ranging from 40-74% with an average of 63.3%. This suggests the possibility of cultivating medicinal plant species on commercial scale. Based on the results, it is suggested that linkages between all stakeholders should be strengthened in order to promote conservation and commercial production of medicinal plants. Furthermore, improving the knowledge-base of scientists, traditional herbal medical practitioners, policy makers and the public on the relevance and safety of traditional plant medicine could lead to the sustainability of the medicinal plants industry in Ghana